Democratic Citizenship Education and Inclusion: Preparing Preservice Teachers for Inclusive Social Studies - Urban, Dennis J. (Journal of the American Academy of Special Education Professionals, 2018)
Students classified with disabilities make up more than 13 percent of the public school population in the United States, but they remain on the margins of social studies research. Thus, we know very little about social studies education in inclusive settings. This study explores how social studies methods classes in one teacher education program prepare teachers for inclusive education. Combining theoretical perspectives from democratic citizenship education and Disability Studies in Education (DSE), this study explores how themes of democracy, community, diversity, disability, and inclusion manifested in two social studies methods classes. Findings indicate the methods instructor encouraged and practiced democratic and inclusive pedagogy, but his approach often met resistance from preservice teachers’ experiences with disability and inclusion, the intransigence of a traditional special education paradigm, and the limitations of diversity education vis-à-vis DSE. Implications for democratic citizenship education, inclusive education, and teacher education are discussed.